A facile method for determining the Fe(0) content and reactivity of zero valent iron. Issue 6 (9th December 2015) - Li, Shaolin; Ding, Yangyang; Wang, Wei; Lei, Hong
Abstract : This work provides a facile and reliable way to assess the quality of metallic iron used for environmental clean-up. Abstract : Zero valent iron (ZVI) is increasingly used in large quantities for water treatment. In large-scale application of ZVI, a common question that engineers encounter is ZVI selection or its quality assurance and quality control (QA/QC). A facile method for assessing ZVI quality is proposed and studied in this work. The method is based on the Fe(iii )–Fe(0) reaction that has a fast reaction rate, a known and simple stoichiometry, and an easy-to-assay product. The method is conducted by mixing the sample ( e.g., testing ZVI) with concentrated Fe(iii ) solution (up to 3.0 g L −1 ) for 3–4 hours. The metallic iron (Fe(0)) content of the sample is obtained by assaying the final increase of the total dissolved iron, and its reactivity is quantified using the observed dissolution rate constants. The method is experimentally validated using 23 iron-based materials. Studies with reference iron powder and iron oxide demonstrate that the Fe(iii ) solution has satisfactory specificity in selecting Fe(0). Replicate experiments and t -test evaluation show the complete dissolution of the Fe(0) content in micron-scale ZVI and the high reproducibility of the method for measuring Fe(0). The accuracy and reliability of the method are studied using 15 commercial ZVIs of known Fe(0) purity, in a series of experiments using Fe(iii ), Cu(ii ) or trichloroethylene. The experiments show that the results from the proposed method are accurate and reliable, and that the method is a strong tool more effective than conventional techniques such as X-ray diffraction and BET-N2 adsorption. This work provides an easy and facile way for the quantitative assessment of the quality of metallic iron used for environmental clean-up, especially for the quick survey of a large number of iron samples on site. The method may also serve as a QA/QC procedure for ZVI in industrial-scale production.